Learning with Trisomy 21: Life Skills Training of a Child with Down's Syndrome (Annals of King Edward Medical University, 2023)
Trisomy 21 is one of the commonly identified genetic causes of Intellectual Disability. Such children experience a lack of attention and neglect by parents and teachers due to their slow response to intervention, which sometimes becomes demotivating for caregivers. However, with the recent medical advances and institutional support, avenues have been opened to help overcome the challenges related to Down's Syndrome. The present case study highlights the life skills training of a 7 year old child with Down's Syndrome, studying in a special education institute of Lahore. The post-assessment showed that consistent practice of behavior modification procedures led to significant improvements in the adaptive functioning of the child.